1988
DOI: 10.2165/00003088-198814010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Ketoconazole

Abstract: Ketoconazole, a synthetic imidazole antifungal, is effective for superficial fungal infections, genital candidosis and chronic mucocutaneous candidosis, and has been used in immunocompromised patients and advanced prostatic carcinoma. Absorption of ketoconazole is variable after oral administration, with large variability in peak serum concentrations. Antacids reduce, and food or dilute hydrochloric acid increase, absorption. Renal failure and bone marrow transplantation are associated with reduced absorption.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
83
2
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(94 citation statements)
references
References 93 publications
(102 reference statements)
8
83
2
1
Order By: Relevance
“…Moreover, CYP3A4 inhibition by ketoconazole, a widely used drug for treating skin and antifungal infections, may be of clinical importance for lithocholic acid homeostasis. The currently recommended daily oral dose for ketoconazole is 200 to 400 mg (Daneshmend and Warnock, 1988;Schäfer-Korting, 1993;Gupta et al, 1994), and peak plasma concentrations of ketoconazole of 2.5 to 4 g/ml or 4.7 to 7.5 M were measured in healthy volunteers after administration of a single oral 200-mg dose (Heel et al, 1982;Gupta et al, 1994). This serum concentration is close to the highest concentration of ketoconazole used in the present study that produced maximal inhibition of lithocholic acid biotransformation.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, CYP3A4 inhibition by ketoconazole, a widely used drug for treating skin and antifungal infections, may be of clinical importance for lithocholic acid homeostasis. The currently recommended daily oral dose for ketoconazole is 200 to 400 mg (Daneshmend and Warnock, 1988;Schäfer-Korting, 1993;Gupta et al, 1994), and peak plasma concentrations of ketoconazole of 2.5 to 4 g/ml or 4.7 to 7.5 M were measured in healthy volunteers after administration of a single oral 200-mg dose (Heel et al, 1982;Gupta et al, 1994). This serum concentration is close to the highest concentration of ketoconazole used in the present study that produced maximal inhibition of lithocholic acid biotransformation.…”
Section: Discussionsupporting
confidence: 54%
“…There have been suggestions that the pharmacokinetics of ketoconazole, another imidazole antifungal drug, may be dose dependent (8). Recently, similar suggestions have been made about the pharmacokinetics of another imidazole, itraconazole (2).…”
mentioning
confidence: 94%
“…To date, changes in the disposition of some substances, including folic acid (16) and clindamycin (13), have been reported. It has been reported that the absorption of ketoconazole is decreased in the presence of a high gastrointestinal pH (3,8,20), a condition which can occur in people with HIV infection because of achlorhydria, although this does not appear to occur with fluconazole (3).…”
mentioning
confidence: 99%
“…For example, in vivo drug interactions in man have been noted with cyclosporin, chlordiazepoxide, methylprednisol, ne and antipyrine (Daneshmend & Warnock, 1988 (Hall et al, 1987). However, the ability of ketoconazole to impair the in vivo metabolism of the anticonvulsant has not been described.…”
Section: Introductionmentioning
confidence: 99%